2000
DOI: 10.1046/j.1467-2494.2000.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram and emulsion stability of surfactant–fragrance systems

Abstract: Emulsions containing 95 wt.% water were prepared of a fragrance oil (limonene, the mixture of limonene and phenethyl alcohol in different ratios, and benzaldehyde), using a commercial tetraethyleneglycol lauryl ether (Laureth 4) as the stabilizer. The emulsion stability was observed both visually and with the aid of a microscope. The variation of emulsion stability with the fragrance/surfactant ratio is related to the phase changes in the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Alcohol-free perfumes based on micro- and nanoemulsions are already present in the patent literature [19,20,21,22], however, apart from additional solubilizers, such as polyols or paraffin hydrocarbons, the compositions of the perfumes in the above-mentioned patents have cationic or anionic surfactants, which can be an irritant to the skin. Nanoemulsions that serve as a matrix for fragrance substances used in cosmetics are also described in the literature [18,23,24,25,26,27,28] these are primarily solutions for emulsification of a single lipophilic component that forms the oil phase of a nanoemulsion (e.g., D-limonene) [18,23,24]. On the other hand, the fragrance compositions contain up to twenty compounds with various chemical structures (alcohols, phenols, aldehydes, esters, saturated, unsaturated, cyclic, and branched hydrocarbons), and as a result they are a difficult base for obtaining stable nanoemulsion systems.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol-free perfumes based on micro- and nanoemulsions are already present in the patent literature [19,20,21,22], however, apart from additional solubilizers, such as polyols or paraffin hydrocarbons, the compositions of the perfumes in the above-mentioned patents have cationic or anionic surfactants, which can be an irritant to the skin. Nanoemulsions that serve as a matrix for fragrance substances used in cosmetics are also described in the literature [18,23,24,25,26,27,28] these are primarily solutions for emulsification of a single lipophilic component that forms the oil phase of a nanoemulsion (e.g., D-limonene) [18,23,24]. On the other hand, the fragrance compositions contain up to twenty compounds with various chemical structures (alcohols, phenols, aldehydes, esters, saturated, unsaturated, cyclic, and branched hydrocarbons), and as a result they are a difficult base for obtaining stable nanoemulsion systems.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Behan et al 6 found that headspace concentrations of benzyl acetate above the surfactant solutions were directly proportional to the phase volume ratio, and in turn could be rationalized in terms of a simple partition model. One of the main methods used to study the interaction of surfactants with perfumes is evaporation measurement.…”
Section: Introductionmentioning
confidence: 99%
“…In both perfume systems, we can find that the original peak of the synthetic perfume decreases and that a novel peak appears at a shorter retention time after the 60minute light irradiation. Hence, dependent on the density of the oil phase and on the phase changes taking place with changing the surfactantperfume ratio [10]. Moreover, we previously investigated the influence of synthetic perfumes on the stability of O/W emulsion [13].…”
Section: Resultsmentioning
confidence: 99%
“…The emulsification makes the heat resistance of synthetic perfumes high and constantly releases fragrance from the product [6,7]. So that, many studies on emulsified perfumes have been undertaken [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%